X-6x-30=2x+4(x-20)

Simple and best practice solution for X-6x-30=2x+4(x-20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-6x-30=2x+4(x-20) equation:


Simplifying
X + -6x + -30 = 2x + 4(x + -20)

Reorder the terms:
-30 + X + -6x = 2x + 4(x + -20)

Reorder the terms:
-30 + X + -6x = 2x + 4(-20 + x)
-30 + X + -6x = 2x + (-20 * 4 + x * 4)
-30 + X + -6x = 2x + (-80 + 4x)

Reorder the terms:
-30 + X + -6x = -80 + 2x + 4x

Combine like terms: 2x + 4x = 6x
-30 + X + -6x = -80 + 6x

Solving
-30 + X + -6x = -80 + 6x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + X + 30 + -6x = -80 + 30 + 6x

Reorder the terms:
-30 + 30 + X + -6x = -80 + 30 + 6x

Combine like terms: -30 + 30 = 0
0 + X + -6x = -80 + 30 + 6x
X + -6x = -80 + 30 + 6x

Combine like terms: -80 + 30 = -50
X + -6x = -50 + 6x

Add '6x' to each side of the equation.
X + -6x + 6x = -50 + 6x + 6x

Combine like terms: -6x + 6x = 0
X + 0 = -50 + 6x + 6x
X = -50 + 6x + 6x

Combine like terms: 6x + 6x = 12x
X = -50 + 12x

Simplifying
X = -50 + 12x

See similar equations:

| (x)(x)+x+4=60 | | 5x-2.1=62.5 | | (2y+2y)+(4x+4x)=30 | | 2(4y-3)=3(y+5) | | 2x+57=33findx | | u+3.14=70 | | 2x+57=33 | | (x+2i)(x-2i)(x+4)=0 | | 6=J-5 | | 3y+7=2x-5 | | N/10-20=20 | | 100x-40y=320 | | 6x7/8= | | 3z+5z=0.6 | | (n)(n)+72=-17n | | 3x-5=6+x | | 6x+7=3(2x+4) | | (k)(k)-11k+30=0 | | (12y)(12y)+40y=7 | | 3x^2-8+5x=0 | | 3x+6=507 | | 10/3x1/2 | | 6d+4=-32 | | 5/6z=5/7 | | 18/sin40 | | a=bd | | p^2-14p=51 | | (d)(d)=5d | | 10c/2-32/4=56/8 | | (w)(w)=12 | | 3/7x1/7 | | 6-9(1-7n)=-21 |

Equations solver categories